Lifetime estrogen exposure and domain-specific cognitive performance: results from the IGNITE study - Watts, Amber; Donofry, Shannon; Ripperger, Hayley; Eklund, Nicole M.; Wan, Lu; Kang, Chaeryon; Grove, George; Oberlin, Lauren E.; Gujral, Swathi; Vidoni, Eric D.; Burns, Jeffrey M.; McAuley, Edward; et al. (Frontiers in Aging Neuroscience, 2025)
IntroductionDisruptions in estrogen exposure (i.e., surgically induced menopause) have been linked to poorer cognitive aging and dementia risk. Hormone therapy use (e.g., birth control, menopausal hormone therapy) has shown mixed associations with cognitive performance, possibly due to limited cognitive test batteries. To address previous inconsistencies, we investigated baseline data from Investigating Gains in Neurocognition in an Intervention Trial of Exercise (IGNITE). We hypothesized that (1) oophorectomy prior to natural menopause would be associated with poorer cognitive performance, (2) timing and duration of birth control and menopausal hormone therapy would influence associations with cognitive performance, and (3) APOE4 carrier status would interact with oophorectomy and hormone therapy to influence cognitive performance.MethodsIn 461 post-menopausal females (M age = 69.6) we assessed oophorectomy and hormone therapy use to examine associations with the Montreal Cognitive Assessment (MoCA) and factor-analytically derived composite scores for episodic memory, processing speed, working memory, executive function/attentional control, and visuospatial processing.ResultsHypothesis (1) We did not observe associations between oophorectomy prior to natural menopause and poorer cognitive performance. However, hormone therapy use, started on average within 2 years of oophorectomy, was associated with better episodic memory (β = 0.106, p = 0.02), working memory (β = 0.120, p = 0.005), and visuospatial processing (β = 0.095, p = 0.03). Hypothesis (2) Birth control use was associated with better performance on the MoCA (β = 0.093, p = 0.04), working memory (β = 0.102, p = 0.02), and executive function/attentional control (β = 0.103, p = 0.02). However, duration and timing of birth control and menopausal hormone therapy were not associated with cognitive performance. Hypothesis (3) We did not observe significant interactions between APOE4 status and oophorectomy or hormone therapy in their associations with cognitive performance.DiscussionOur results suggest exposure to estrogen during adulthood, specifically birth control and hormone therapy among women undergoing pre-menopausal oophorectomy, benefits cognitive function in older adulthood. Our comprehensive cognitive battery allowed us to examine cognitive function with a high degree of granularity. Future work should evaluate causal mechanisms of associations between lifetime estrogen exposure and later life cognitive function.